2002
DOI: 10.2134/agronj2002.0081
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date, Cultivar, and Tillage System Effects on Dryland Soybean Production

Abstract: on yield-enhancing production practices such as tillage system, planting date, and cultivar selection. Soybean [Glycine max (L.) Merr.] yields from nonirrigated fieldsTillage systems can impact soil moisture status bein the midsouthern USA have consistently lagged behind those from cause tillage influences infiltration, runoff, evaporation, irrigated fields. Nonetheless, nonirrigated fields still attract a larger and soil water storage. With conventional tillage, weeds share of soybean acreage in this region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 9 publications
3
25
0
1
Order By: Relevance
“…The sowing date is possibly the main and less expensive crop management, which impacts the soybean grain yield (Popp et al, 2002;Robinson et al, 2009). In soybean crop, early sowing can increase grain yield (Wilcox & Frankenberger, 1987) or not change it (Grau et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The sowing date is possibly the main and less expensive crop management, which impacts the soybean grain yield (Popp et al, 2002;Robinson et al, 2009). In soybean crop, early sowing can increase grain yield (Wilcox & Frankenberger, 1987) or not change it (Grau et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al (2004) conducted an experiment and stated that earlier planting led to an increase in the number of seeds, in the number of pods, and in the harvest index, but that the number of seeds per pod declined, compared to later planting dates. Pop et al (2002) concluded, from the experiment they had conducted, that if the planting of cultivars with unlimited growth was delayed from the 23 rd day of the second month in spring to the 15 th day of the first month in summer, the height of the plants and the number of nodes on the main stem would decrease , while in cultivars with unlimited growth planted after the end of spring these features did not show a decline and decreases in yield were observed in crops planted after the first half of the last month of spring. McWilliams et al (2004) evaluated the effects of minimizing delays in planting and the environmental stresses on optimizing seed yield , and found out that second crop or late planted soybean, compared to the first crop soybean, was influenced by the two important factors of temperature and day length (which increased and decreased, respectively, in summer).…”
Section: Introductionmentioning
confidence: 99%
“…The comparative economics of tillage can vary by region, cropping system, variable input costs, risk aversion, and management experience among other factors. The economics of studies utilizing older technology also do not apply very well to current conditions (8,11,15,21,26,38, 63,64,65,74,78,79,80,82,86,96, 106,108,109).…”
Section: Introductionmentioning
confidence: 99%